Manajemen Dakwah Safari Romadlon Santri Darussalam Sumbersari Kencong Kepung Kediri - Rohmad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
This study aims to see the extent of the management of da'wah Safari Romadhon santri Darussalam Sumbersari, Kencong, Kepung, Kediri. Using a qualitative approach, and type of case study research, this research resulted in the conclusion that the management of Safari Romadhon santri Darussalam Sumbersari has been very good and running in an orderly manner, among others by looking at the practice carried out by the Safari Committee Romadlon by training the members of the Safari Romadlon, facilitated da'wah books and there is always continuous monitoring from the committee. Besides, by registering the areas that asked to be parachuted santri, santri was given the task to become a priest praying five times at once as speakers, and also the main mission of safari practice Romadlon is Nasyrul Ilmi Waddin in accordance with the voice of founder pondok pesantren Darussalam.